# p3 help

Watch
Announcements
This discussion is closed.
#1
how would u expand (cot^2(3x))

would u get

(cosec3x-1)^2

which equals

cosec^2(3x) - 2cosec3x + 1

or does it equal

cosec^2(9x) - 2cosec3x + 1

im confused
0
#2
oh and how would u intergrate it
0
15 years ago
#3
cot^2(3x) = cosec^2(3x) - 1

Int. cot^2(3x) dx. = Int. cosec^2(3x) - 1 dx. = -cot(3x)/3 - x + k = k - [cot(3x)/3 + x]
0
#4
(Original post by Nima)
cot^2(3x) = cosec^2(3x) - 1

Int. cot^2(3x) dx. = Int. cosec^2(3x) - 1 dx. = -cot(3x)/3 - x + k = k - [cot(3x)/3 + x]
thanks
0
X
new posts
Back
to top
Latest
My Feed

### Oops, nobody has postedin the last few hours.

Why not re-start the conversation?

see more

### See more of what you like onThe Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

### Poll

Join the discussion

#### How will you be receiving your results?

Going into school to pick them up (181)
33.39%
Receiving them online / by email (270)
49.82%
I still don't know (91)
16.79%